1992
DOI: 10.1002/cd.23219925706
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-child relationships and the process of adjusting to school

Abstract: Research on teacher-child relationships is based on two foundations: (1) the common experience of teachers, parents, and children that the child's relationship with his or her teacher is an especially important component of the school experience and related to child adjustment and (2) research in social development, attachment theory, and teaching and learning that increasingly shows the importance of adult-child relationships as contexts for development. The present study blends theory on child-adult attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
218
1
23

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(248 citation statements)
references
References 14 publications
6
218
1
23
Order By: Relevance
“…Previous researchers have demonstrated an effect of student antisocial conduct on TSRQ (Birch & Ladd, 1997, 1998Ladd et al, 1999;Pianta & Steinberg, 1992;Pianta & Stuhlman, 2004). Similarly, it is reasonable to expect that teachers will also find it easier to show support and affection to students who try hard and attend to instructions.…”
Section: Reciprocal Effects Among Tsrq Effortful Engagement and Achmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous researchers have demonstrated an effect of student antisocial conduct on TSRQ (Birch & Ladd, 1997, 1998Ladd et al, 1999;Pianta & Steinberg, 1992;Pianta & Stuhlman, 2004). Similarly, it is reasonable to expect that teachers will also find it easier to show support and affection to students who try hard and attend to instructions.…”
Section: Reciprocal Effects Among Tsrq Effortful Engagement and Achmentioning
confidence: 95%
“…On the basis of attachment theory perspectives (Bowlby, 1980), a close and supportive relationship with one's teacher would be expected to promote a child's emotional security and confidence. A secure relationship with the teacher may serve as a resource that permits young students to actively explore their environment and to cope more effectively with novel academic and social demands (Howes et al, 1994;Pianta & Steinberg, 1992). Drawing from this reasoning, Little and Kobak (2003) expected and found that among elementary children, emotional security with the teacher attenuated children's stress reactivity to negative teacher and peer events in the classroom.…”
Section: Effect Of Tsrq On Effortful Engagementmentioning
confidence: 99%
“…The type of relationship between the teacher and the student serves as a connection between the two, providing a better atmosphere for a classroom environment (Jones et al, 1981). In a series of descriptive studies, Pianta and Steinberg (1992) and Pianta (1994) showed dimensions of closeness, conflict, and dependency instructor relationship behaviours as perceived and reported by the students to characterise instructor-student relationship. Students who reported more positive involvement with their teachers were found to score high on closeness (secure relationship) sub scale items.…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…The teacher may serve as an attachment figure for young children, such that a secure and close relationship with the teacher enables children to cope better with social and academic challenges in preschool and the early elementary grades (Howes et al, 1994;Pianta & Steinberg, 1992;Sroufe, 1983;van Ijzendoorn, Sagi, & Lambermon, 1992). Children who enjoy supportive relationships with teachers and peers are expected to gain confidence in their abilities and to be more motivated to participate in classroom activities (Birch & Ladd, 1997;Gest, Welsh, & Domitrovich, 2005;Ladd et al, 1999;Skinner & Belmont, 1983).…”
Section: Introductionmentioning
confidence: 99%